Assessment of Upper Extremities Using an Interactive Robotics Rehabilitation Training System - Ho, Sharon Siew Wan (Universiti Teknologi PETRONAS, 2017)
'Subject-Oriented' approach expands the cooperation and desire of the patients bit by bit but they need to remind the patient of their capacity to make progress in their attempts of muscle activation. Hence, preparing and appraisal situations for the execution of ADLs are essential for the usage robotics rehabilitation system. This study intends to research on the legitimacy of 'subject-oriented' approach in helping the patient's movement and attempt as shown by one's capacity. On that record, it is assumed that 'subject-oriented' approach will amplify the result. This robot intervened treatment ought to be as successful and proficient as that of an affirmed human therapist in enhancing versatility and scope of movement and will just help the development of the patient just as much as fundamental in a shorter timeframe while persistent giving quantitative information for better change through the rehabilitation procedure.